Relationship Between Morning Heart Rate Variability and Creatine Kinase Response During Intensified Training in Recreational Endurance Athletes - Weippert, Matthias; Behrens, Martin; Mau-Moeller, Anett; Bruhn, Sven; Behrens, Kristin (Frontiers in Physiology, 2018)
Specific physiological responses and their relationship were analyzed in 12 recreational endurance athletes (43.8 ± 7.9 years) during a period of intensified cycling training. Heart rate (HR), HR variability (HRV), serum creatine kinase (S-CK) and haematocrit (Hct) were measured in the mornings before (PRE) and following three consecutive days of intensified training (POST 1-3). Morning HR increased during this period (PRE: 52.2±6.7 bpm, POST 1: 58.8±7.0 bpm POST 2: 58.5±8.1 bpm, POST 3: 57.9±7.2 bpm; F(3,33) = 11.182, p < 0.001, ηp2 = 0.554). Parasympathetic HRV indices decreased from PRE to POST (F(3,33) ≥ 11.182, p < 0.001, ηp2 ≥ 0.563), no effect was found for sympathetically modulated HRV (F(3,33) = 2.287, p = 0.101, ηp2 = 0.203). Hct decreased (PRE: 49.9±4.0%, POST 1: 46.5±5.1%, POST 2: 45.5±3.8%, POST 3: 43.2±3.4%; F(3,33) = 11.909, p < 0.001, ηp2 = 0.520) and S-CK increased during the training period (PRE: 90.0±32.1 U/L, POST 2: 334.7±487.6 U/L, POST 3: 260.1±303.4 U/L, POST 3: 225.1±258.8 U/L; (F(3,33) = 3.996, p = 0.017, ηp2 = 0.285). S-CK release was associated with HR (r = 0.453, p = 0.002, n = 44), RMSSD (r= -0.494, p= 0.001, n = 44) and HF-Power (r = -0.490, p = 0.001, n = 44). A period of intensified training was associated with haemodilution, parasympathetic withdrawal and S-CK-increase. Cardiac autonomic control at morning rest correlated with the S-CK-release; and thus, may serve as a practical mean to complementary monitor and prescribe training load in this population.